AN INVESTIGATION INTO THE USAGE OF LEAN CONSTRUCTION TECHNIQUES IN NIGERIA - Olatunji J OLADIRAN (Journal of Construction Project Management and Innovation)
Inadequate implementation of lean construction techniques poses a serious problem to the Nigerian construction process. The usage of lean techniques at the early stage of construction projects results in enhanced environmental performance, waste reduction, an increase in profits, and sustainable construction, among other things. This study focuses on the implementation of lean techniques, with a view to enhancing their usage, thereby improving the performance of construction projects. It examines the lean construction techniques that are used, as well as the extent of their usage, the implementation processes that are used, the benefits of improving usage of lean construction techniques in the study area, and the measures used to improve implementation of such techniques. In achieving these objectives, construction professionals from 10 organisations in Lagos State, Nigeria, were interviewed on 12 selected lean techniques. The data were analysed using descriptive statistics tools, namely means, frequencies, percentages, and modes. The findings reveal that fail-safe quality and safety, daily huddle meetings, increased visualisation, and the 5S process are poorly used, while the other eight techniques, namely Last Planner® System (LPS®), first-run studies, just-in-time (JIT), total production maintenance, concurrent design, kaizen, design for buildability, and supply chain management, are not used at all. Nevertheless, application of the aforementioned first four techniques has contributed to improved workflow on sites, maintenance of good site organisation, and increased job satisfaction among employees. It is recommended that top management, professional bodies, and institutions of higher learning make it a priority to offer education and training programmes on the concept of lean for workers on construction projects. Government should promote the concept of lean techniques, so as to encourage a culture of safety and improve productivity and performance on construction projects.